Comparative Studies of Steel, Bamboo and Glass Fiber as Reinforcing Bars in Concrete Tensile and Flexural Characteristics - Sukant Sahu; Ravindra Kumar Raj (International Journal of Scientific Research in Civil Engineering, 2021)
This study comparatively evaluated the flexural performance and deformation characteristics of concrete elements reinforced with bamboo (Bambusa vulgaris), Glass fiber and the twisted steel rebars. The yield strength (YS), ultimate tensile strength (UTS) and the elongation of 9 specimens of the three materials were determined using a universal testing machine. These beams of concrete strength 25 N/mm2  at age 7, 14 and 28 days were separately reinforced with bamboo, glass fiber and steel bars of same percentage, while the stirrups were essentially mild steel bars. It is Determined that out of three which material sample is suitable rebars for non-load bearing and lightweight RC flexural structures also bonding and load-carrying capacity.
Keywords: Deformation; Concrete Beam; Reinforcement; Tensile Strength; Fiber